The determining key factors of the economic path of a complex fishery: the case study of the French commercial fishing in the Bay of Biscay - Steinmetz, Fabien (CCSD, 2010)
The average trophic level of the landings of the species landed by the french fleets in the Bay of Biscay is dropping since 30 years, according to the worldwide range observations of Daniel Pauly. The effects of the ecosystemic, institutional and economic factors of this drop are studied with two complementary approaches, a time series analysis and the interpretation of the phenomenons thanks to a bio-economic model. The major factors which could interact with the exploitation from 1973 to nowadays have been analysed. The short term study of the productions and the productivity of tree large trawler fleets from south brittany showed that they adapted according to their specificities to the constraints enforced by the stocks or the prices. At the larger case of the aggregated landings coming from the maritime area of the Bay of Biscay or the North-East Atlantic, we put in a obvious place the links between the evolution of the landing's structure and of the biologic or economic factors, revealing particularly the rise of the pelagic landings. We observe that there is a relation between the price of imports and french landings prices, this link depending on the kind of fish market studied. A bio-economic model, based on the Gordon-Schaefer hypothesis enlarged to a predator-prey or competition system, shows the long term effects produced by the changes of technical progress, the regulation mode and the equilibrium price on the landings structure, some of these changes explaining the structural change of the landings observed in the Bay. Mots clés : Economie des ressources naturelles renouvelables, modélisation bioéconomique, théorie du producteur et du consommateur, approche éco-systémique, théorie des indices, analyse de données, chaîne trophique, pêche fraîche française, Golfe de Gascogne Le niveau trophique moyen des espèces débarquées par les flottilles françaises du Golfe de Gascogne a baissé depuis 30 ans suivant en cela les observations de Daniel Pauly au niveau mondial. Les effets des déterminants ...